CATCALLING PHENOMENON AS A FORM OF SEXUAL HARASSMENT VERBALLY AGAINST WOMEN IN MALANG EMMANUEL LEVINAS FACE PHILOSOPHY PERSPECTIVE - Kwirinus, Dismas; Pandor, Pius (Universitas Tanjungpura, 2023)
This research aims to explain the phenomenon of catcalling as a form of verbal sexual harassment against women in Malang from the perspective of Emmanuel Levinas' facial philosophy. This catcalling terminology emerged from several large urban areas in Indonesia, such as Jakarta, Malang, Yogyakarta and Surabaya. Catcalling is called verbal sexual harassment because the perpetrator responds to the victim, such as whistling, sexually nuanced remarks in the form of words that make the victim uncomfortable, feel humiliated and attack the victim's sexual attributes. Among urban communities, the term catcalling has a vague meaning because it is a joke or joke to victims, most of whom are women. This paper aims to describe, analyze and find out the form of communication from catcalling. The author uses a phenomenological analysis methodology. The type of research used is qualitative research methods: a critical reading of the text and observations. As for the findings in this study, they were catcalling, verbal sexual harassment and rape culture. For Levinas, the victim or woman who experiences catcalls is the other who is tortured and harmed.